2014
DOI: 10.2478/aicu-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic 1-Type Curves and Weak Biharmonic Curves in Lorentzian 3-Space

Abstract: We study 1-type curves by using the mean curvature vector field of the curve. We also study biharmonic curves whose mean curvature vector field is in the kernel of Laplacian. We give some theorems for them in the Euclidean 3-space. Moreover we give some characterizations and results for a Frenet curve in the same space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The Cartan frame is a frame with the minimum number of curvature functions which are invariant under Lorentzian transformation (see [11][12][13]19]).…”
Section: Null Slant Curvesmentioning
confidence: 99%
“…The Cartan frame is a frame with the minimum number of curvature functions which are invariant under Lorentzian transformation (see [11][12][13]19]).…”
Section: Null Slant Curvesmentioning
confidence: 99%
“…In [2], Kılıç and Arslan studied Euclidean submanifolds satisfying ∆ ⊥ H = λH. In [12], Kocayigit and Hacısalihoglu studied curves satisying ∆H = λH in a 3-dimensional Riemannian manifold. For Legendre curves in Sasakian manifolds, same problems were studied by Inoguchi in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to meticulous studies, it has been revealed that curves can be classified [6]. After this classification, a great many number of articles have been written, [7,8] and also [9]. In this paper, we first take a unit speed curve which we call through the work as main curve, then write the characterizations of an involute curve by means of Frenet apparatus of the main curve.…”
Section: Introductionmentioning
confidence: 99%
“…is called a Laplace operator [7,8]. Let α be the unit speed curve and H be the mean curvature vector field along the curve α.…”
Section: Introductionmentioning
confidence: 99%